2017
DOI: 10.1002/nop2.85
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and carriers: a multicenter survey of nurses’ barriers and facilitators to monitoring of nurse-sensitive outcomes in intensive care units

Abstract: AimTo identify nurses’ barriers and facilitators to monitoring of nurse‐sensitive outcomes in intensive care units (ICUs), and to explore influential nurse characteristics and work environment factors.DesignA cross‐sectional survey in three Dutch ICUs between October 2013 ‐ June 2014.MethodsA questionnaire with questions regarding facilitators and three types of barriers: knowledge, attitude and behaviour. The Dutch Essentials of Magnetism II was used to examine work environments.ResultsAll 126 responding nurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Recent studies indicate that the resources—such as time—that nurses have, nurses' work experience and nurse‐to‐patient ratios affect the extent to which nurses complete patient care tasks such as the monitoring of patients' fluid intake (Litchfield, Magill, & Flint, ) and the taking of patients' vital signs (Recio‐Saucedo et al, ). The delivery and monitoring of these tasks are important because they are within nurses' scope of practice and they directly affect patients' health outcomes (Stalpers, De Vos, Van Der Linden, Kaljouw, & Schuurmans, ). Such nuances in nurses' work, nurses' qualifications and motivations as well as the challenges that nurses confront daily highlight salient factors that facilities must constantly evaluate as they ascertain and manage the staffing mix appropriate for their respective circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicate that the resources—such as time—that nurses have, nurses' work experience and nurse‐to‐patient ratios affect the extent to which nurses complete patient care tasks such as the monitoring of patients' fluid intake (Litchfield, Magill, & Flint, ) and the taking of patients' vital signs (Recio‐Saucedo et al, ). The delivery and monitoring of these tasks are important because they are within nurses' scope of practice and they directly affect patients' health outcomes (Stalpers, De Vos, Van Der Linden, Kaljouw, & Schuurmans, ). Such nuances in nurses' work, nurses' qualifications and motivations as well as the challenges that nurses confront daily highlight salient factors that facilities must constantly evaluate as they ascertain and manage the staffing mix appropriate for their respective circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical sites that are outward-facing and well-networked are adept at introducing and implementing external strategies (including policy, regulation, guidelines, and QCP-M) and using available resources to spread the intervention. Nurses and midwives in these sites engage with provided resources (such as champions and materials), resulting in an increased chance of intervention success [33,36,[38][39][40].…”
Section: Theory Refinementmentioning
confidence: 99%
“…Where interventions are supported at a national level [38] by an implementation framework [40] and organizations are externally facing, then there is a more standardized approach to implementation [33], leading to successful adoption of the intervention. Clinical sites that show readiness for QCP-M implementation have strong internal networks and communication systems that facilitate a practice culture compatible with the introduction of quality interventions and a learning climate supportive of nurses and midwives who are implementing the QCP-M, resulting in an increased chance of the intervention becoming embedded in practice [34,36,[38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57].…”
Section: Theory Refinementmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, a survey on nurses’ attitudes to PU prevention (Unver, Findik, Ozkan, & Surucu, ) found that previous PU care education significantly affected nurses’ attitudes. A multicentre survey aimed at identifying barriers and facilitators to the monitoring of nurse‐sensitive outcomes in intensive care units found that education and clear management policy were important facilitators (Stalpers, De Vos, Van Der Linden, Kaljouw, & Schuurmans, ). In this study, nurses identified PUs and patient satisfaction as outcomes falling squarely within nurses’ responsibility.…”
Section: Introductionmentioning
confidence: 99%